Clean bill of health? Towards an understanding of health risks posed by urban ibis. Issue 1 (29th May 2019) - Maute, Kimberly; Webb, Cameron; Phalen, David; Martin, John; Hobson-Peters, Jody; Major, Richard E; French, Kristine
Abstract: Urban waterbirds are considered both serious pests and inspiring wildlife. Ibis and gulls are often vilified due to their dirty appearance and disruption of outdoor activities, while ducks are affectionately fed in parks. However, all waterbirds are potential reservoirs of zoonotic pathogens. In Sydney (Australia), we documented the relative prevalence of arbovirus exposure and Salmonella shedding in 72 Australian White Ibis ( Threskiornis moluccus ) at 2 urban sites in 2003 during a management cull and in 2015 as a response to increased public interest. We sampled during a period of peak human arbovirus and Salmonella infection risk in late summer and early autumn. In 2015, antibodies for the endemic West Nile virus Kunjin strain (WNVKUN ) were detected in one bird. While not indicative of immediate public health risk, this highlights that an animal with a history of exposure was present or moved into a region not previously known to have endemic WNVKUN activity. However, the movement patterns of this individual and WNVKUN host competency of this species are unknown. An absence of other antibody responses suggests that ibis are not important viral reservoirs or flaviviruses are not widespread in Sydney. Assays failed to detect Salmonella in 2015, but 25% of individuals were positive in 2003. Further monitoring of the arguable health hazard represented by urban T. moluccus will facilitate informed decisions and solutions to urban bird and wetland management challenges.